2017
DOI: 10.4103/0976-9668.198356
|View full text |Cite
|
Sign up to set email alerts
|

Adult-to-adult living donor liver transplantation: Operative techniques to optimize the recipient's outcome

Abstract: Adult-to-adult living donor liver transplantation (LDLT) is widely accepted today with good outcomes and safety reported worldwide for both donor and recipient. Nonetheless, it remained a highly demanding technical and complex surgery if undertaken. The last two decades have seen an increased in adult-to-adult LDLT following our first report of right lobe LDLT in overcoming graft size limitation in adults. In this article, we discussed the operative techniques and challenges of adult right lobe LDLT incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Management of biliary strictures with endotherapy, i.e ., ERC with endobiliary stenting, is the treatment of choice especially for patients with AS[ 22 ]. They are notoriously difficult to treat with a recurrence rate between 9%-37%[ 23 ]. However, contrary to this, a report from the Adult-to-Adult Living Donor Liver Transplantation Cohort Study consortium (A2ALL)[ 24 ] suggested a comparable efficacy of endoscopic treatment in anastomotic strictures (in both DDLT as well as LDLT setting) based on which a recommendation to reserve endoscopic therapy as a first line treatment for all patients with anastomotic strictures could be made[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of biliary strictures with endotherapy, i.e ., ERC with endobiliary stenting, is the treatment of choice especially for patients with AS[ 22 ]. They are notoriously difficult to treat with a recurrence rate between 9%-37%[ 23 ]. However, contrary to this, a report from the Adult-to-Adult Living Donor Liver Transplantation Cohort Study consortium (A2ALL)[ 24 ] suggested a comparable efficacy of endoscopic treatment in anastomotic strictures (in both DDLT as well as LDLT setting) based on which a recommendation to reserve endoscopic therapy as a first line treatment for all patients with anastomotic strictures could be made[ 22 ].…”
Section: Discussionmentioning
confidence: 99%